THE EARTHQUAKE-RESISTANT BUILDING ASSISTANCE IN JATISARI VILLAGE KEDUNGREJA DISTRICT CILACAP REGENCY: PENDAMPINGAN BANGUNAN TAHAN GEMPA DI DESA JATISARI KECAMATAN KEDUNGREJA KABUPATEN CILACAP - Ferdinandes Eddy Poerwodihardjo; Dwi Istiningsih; Dadi Triawan Selalatu (WIKUACITYA: Jurnal Pengabdian Kepada Masyarakat, 2026)
A house is a basic human need that functions not only as a shelter but also as a space for physical and mental growth and development. In Indonesia, the risk of earthquakes is very high due to its location at the convergence of three major tectonic plates: the Indo-Australian Plate, the Eurasian Plate, and the Pacific Plate. This condition highlights the importance of understanding and applying earthquake-resistant building principles to minimize structural damage and casualties. This community service program aimed to enhance residents’ knowledge and skills in planning and constructing simple earthquake-resistant houses. The activities were carried out in Jatisari Village, Kedungreja District, Cilacap Regency, through educational workshops and direct assistance in building a model house. The materials presented included fundamental principles of earthquake-resistant construction, appropriate material selection, simple and symmetrical floor plan design, structural integration of foundations, tie beams, columns, and ring beams, as well as proper construction techniques. The program was implemented in three stages: preparation (site survey, planning, and cost estimation), construction carried out collaboratively through community participation, and final reporting. The results indicated an improvement in community understanding of earthquake-resistant construction techniques, appropriate material selection, and the importance of proper structural connections between building components. In addition to providing technical skills, the program strengthened social cohesion among residents. With correct construction techniques and relatively minimal additional costs, simple earthquake-resistant houses can be developed to create safer, more resilient, and sustainable living environments in disaster-prone areas